A limited positioning system for memory. Issue 6 (2nd May 2015) - Shapiro, Matthew
ABSTRACT: The 2014 Nobel Prize for Physiology or Medicine is an enormous triumph for John O'Keefe and May‐Britt and Edvard Moser and an historic event for cognitive and behavioral neuroscience. Neuronal representations decoded from action potentials form a mechanistic bridge between brain and mind and demonstrate the continuity of psychology with biology and physical science. The cognitive map theory powered an ongoing, international research program inspired by Hebb (1949 The Organization of Behavior. New York, NY: Wiley) that showed the way toward linking specific patterns of neuronal activity to high level representation and processing. The prize celebrates a path that led from fundamental, philosophical questions about psychological space to enduring, scientific facts: place, head direction, grid, and boundary fields in the hippocampus, presubiculum, entorhinal cortex, and other brain circuits provide a cellular basis for spatial behavior, learning, and memory. By awarding this prize, the Nobel committee affirmed neuroethology and comparative psychology, marked the end of a chapter in one debate about the existence of animal cognition, and recognized cognitive neurophysiology. The "inner GPS" in the brain" demonstrates "a cellular basis for higher cognitive function." Animals represent, process, and use information defined by abstract relationships among items (O'Keefe and Conway, 1978 ) to guide flexible, goal‐directed actions. Beyond raising the ontological status of "animal mind, " the committee agreed that abstract mental representations can be investigated rigorously by recording single unit activity in the brain of behaving animals. © 2015 Wiley Periodicals, Inc.